Is chronic inhibition of phosphodiesterase type 5 cardioprotective and safe? A meta-analysis of randomized controlled trials - Giannetta, Elisa (BioMed Central, 2014)
BACKGROUND: The myocardial effects of phosphodiesterase type 5 inhibitors (PDE5i) have recently received consideration in several preclinical studies. The risk/benefit ratio in humans remains unclear. METHODS: We performed a meta-analysis of randomized, placebo-controlled trials (RCTs) to evaluate the efficacy and safety of PDE5i on cardiac morphology and function. From March 2012 to December 2013 (update: May 2014), we searched English-language studies from MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials and SCOPUS-selecting RCTs of continuous PDE5i administration that reported cardiovascular outcomes: cardiac geometry and performance, afterload, endothelial function and safety. The pooled estimate of a weighted mean difference between treatment and placebo was obtained for all outcomes using a random effects model. A test for heterogeneity was performed and the I(2) statistic calculated. RESULTS: Overall, 1,622 subjects were treated, with 954 randomized to PDE5i and 772 to placebo in 24 RCTs. According to our analysis, sustained PDE5 inhibition produced: (1) an anti-remodeling effect by reducing cardiac mass (−12.21 g/m(2), 95% confidence interval (CI): −18.85; −5.57) in subjects with left ventricular hypertrophy (LVH) and by increasing end-diastolic volume (5.00 mL/m(2); 95% CI: 3.29; 6.71) in non-LVH patients; (2) an improvement in cardiac performance by increasing cardiac index (0.30 L/min/m(2), 95% CI: 0.202; 0.406) and ejection fraction (3.56%, 95% CI: 1.79; 5.33). These effects are parallel to a decline of N-terminal-pro brain natriuretic peptide (NT-proBNP) in subjects with severe LVH (−486.7 pg/ml, 95% CI: −712; -261). PDE5i administration also produced: (3) no changes in afterload parameters and (4) an improvement in flow-mediated vasodilation (3.31%, 95% CI: 0.53; 6.08). Flushing, headache, epistaxis and gastric symptoms were the commonest side effects. CONCLUSIONS: This meta-analysis suggests for the first time that PDE5i have anti-remodeling properties and improve cardiac inotropism, independently of afterload changes, with a good safety profile. Given the reproducibility of the findings and tolerability across different populations, PDE5i could be reasonably offered to men with cardiac hypertrophy and early stage heart failure. Given the limited gender data, a larger trial on the sex-specific response to long-term PDE5i treatment is required. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12916-014-0185-3) contains supplementary material, which is available to authorized users.